EMPOWERING THE ‘MINISTER OF FINANCE’: AN EFFORT TO IMPROVE THE FINANCIAL LITERACY OF HOUSEWIVES - Nasution, Bismar; Siregar, Mahmul; Sukarja, Detania; Lubis, Tri Murti (Talenta Publisher, 2018)
Financial literacy is an important part of financial sector consumer protection. With financial literacy, the community will be able to choose financial products and services that are appropriate to their needs and have the ability to do better financial planning. Data shows that housewives have low financial literacy and, hence, are vulnerable to fraud and scams. Fraud and suspicious fundraising activities are still prevalent in many cities all over Indonesia, including Medan. Training of financial literacy and the legal protection in investment for housewives were designed and implemented to help overcome this issue. The training took place in Medan Selayang and Medan Maimun Districts and aimed to improve housewives’ financial literacy, including on how to manage household money properly and safely so as not to get trapped in bad investment, as well as to educate them about the legal measures that can be taken if they become victims of fraud. The training was conducted using lecture method followed by discussion and consultation. The participants were provided pocket books that were designed to be easily read and understood. Questionnaires were also prepared to measure the knowledge of the participants before and after training. The result of the test shows that the participants’ financial literacy improved after the training.